2007
DOI: 10.1093/jxb/erm067
|View full text |Cite
|
Sign up to set email alerts
|

Response of photosynthetic apparatus to moderate high temperature in contrasting wheat cultivars at different oxygen concentrations

Abstract: The photosynthetic responses to moderately high temperatures (38 degrees C, imposed at 21% or 2% O(2) in air and 1500 mumol m(-2) s(-1)) were compared in wheat (Triticum aestivum L.) cultivars grown in northern regions of Ukraine and expected to be relatively sensitive to high temperatures ('North' cultivars) and in cultivars grown in southern regions and expected to be relatively heat-tolerant ('South' cultivars). Heating intact leaves in 21% O(2) for 1 h decreased CO(2) assimilation by c. 63% in 'North' cult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 50 publications
0
10
0
3
Order By: Relevance
“…Entre los parámetros fisiológicos más importantes para evaluar la respuesta fisiológica de la planta, se encuentran los de intercambio gaseoso como fotosíntesis y transpiración, fuertemente controlados por factores ambientales como la luz y la temperatura que pueden reducir la asimilación de CO 2 , disminuir la producción de carbohidratos o incluso ocasionar un daño irreversible sobre el aparato fotosintético (Zhou et al, 2014;Stasik y Jones, 2007). La fluorescencia de la clorofila que brinda información sobre el estado del fotosistema II y de la presencia de algún estrés biótico o abiótico en la planta (Baker, 2008;Maxwell y Johnson, 2000), y el potencial hídri-co, además de determinar el estado hídrico de la planta, se identifican los puntos más críticos a lo largo del día y en prealba (Zhou et al, 2014;Eamus et al, 2006).…”
Section: Introductionunclassified
“…Entre los parámetros fisiológicos más importantes para evaluar la respuesta fisiológica de la planta, se encuentran los de intercambio gaseoso como fotosíntesis y transpiración, fuertemente controlados por factores ambientales como la luz y la temperatura que pueden reducir la asimilación de CO 2 , disminuir la producción de carbohidratos o incluso ocasionar un daño irreversible sobre el aparato fotosintético (Zhou et al, 2014;Stasik y Jones, 2007). La fluorescencia de la clorofila que brinda información sobre el estado del fotosistema II y de la presencia de algún estrés biótico o abiótico en la planta (Baker, 2008;Maxwell y Johnson, 2000), y el potencial hídri-co, además de determinar el estado hídrico de la planta, se identifican los puntos más críticos a lo largo del día y en prealba (Zhou et al, 2014;Eamus et al, 2006).…”
Section: Introductionunclassified
“…Decreased NR activity indicated that the amount of ammonium from NR catalyzing was reduced. So the increased ammonium content in HT- stressed seedlings was mainly caused by enhanced photorespiration indicated by the contents of photorespiratory amino acids (Dimartino et al 1999), and previous studies also showed that HT-stressed wheat seedlings exhibited higher photorespiratory rate (Stasik and Jones 2007). The increased ammonium content was responsible for the enhanced NADH-GDH activity, because ammonium might be a signal inducing the enzyme activity (Ferrario-Mery et al 2002).…”
Section: Discussionmentioning
confidence: 86%
“…They reported that the decrease of both carboxylation efficiency and photochemical efficiency indicated the Calvin cycle impaired and electron transport damaged, respectively. Stasik and Jones (2007) also used the method of A-C i curve to analyze the Rubisco activity in wheat at moderately high temperature. Additionally, Somersalo and Krause (1989) reported that fully dark condition was helpful for repairing the damaged components of PSII, moreover, weak light intensity, approximately 10-30 µmol m -2 s -1 , was found to help recover damaged PSII components.…”
Section: Effects Of Elevated Temperature On Psiimentioning
confidence: 99%